Life cycles of dominant mayflies (Ephemeroptera) on a torrent of the high Bolivian Andes - Molina, Carlos I. (2016)
The mayflies of the temperate and cold zones have well-synchronized life cycles, distinct cohorts, short emergence and flight periods. In contrast, aquatic insects from the tropical zones are characterized by multivoltine life cycles, “non-discernible cohorts” and extended flight periods throughout the year. This report is the first observation of life cycle patterns made of two species of mayflies on a torrent in the high elevation Bolivian Andes. The samples were taken from four sites and four periods during a hydrological season. The life cycle of each species was examined using size-class frequency analysis and a monthly modal progression model (von Bertalanffy's model) to infer the life cycle synchrony type. These first observations showed a moderately synchronized univoltine life cycle for Andesiops peruvianus (Ulmer, 1920), whereas Meridialaris tintinnabula Pescador and Peters (1987), had an unsynchronized multivoltine life cycle. These results showed that the generalization of all aquatic insects as unsynchronized multivoltine species in the Andean region may not be entirely accurate since there is still a need to further clarify the life cycle patterns of the wide variety of aquatic insects living in this high elevation tropical environment.